DAMPAK KINERJA BAURAN PEMASARAN JASA DAN HUBUNGAN PELANGGAN TERHADAP NILAI PELANGGAN INDUSTRI BROADBAND DI JAWA BARAT - jurnal khitabah (Sekolah Tinggi Agama Islam Putra Galuh Ciamis, 2024)
This study aims to examine the effect of service marketing mix performance and relationship marketing on Broadband Industry customer value in West Java through a survey to Broadband Industry customers in West Java. The research was conducted using quantitative methods. The unit of research analysis is Broadband Industry customers in the West Java region, so the population in this study is customers in the research area. Samples were taken as many as 100 respondents. The sampling technique used in this research is multistage random sampling. The data is processed using Partial Least Square (PLS). The results of this study reveal that service marketing mix performance and relationship marketing have an effect on increasing Broadband Industry customer value in West Java, but service marketing mix performance has a more dominant influence than relationship marketing. Relationship marketing has little effect on customer value creation. The findings of this study provide managerial implications for Broadband Industry management that efforts to improve sustainable marketing performance need to be encouraged to develop a service marketing mix performance that is able to increase customer value. The development of service marketing mix performance needs to be prioritized on the process aspect, which is supported by development on the aspects of people, product, promotion, price, place, and physical evidence.